2021
DOI: 10.1016/j.mmcr.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated pulmonary aspergillosis in ICU patients: Report of five cases from Argentina

Abstract: Invasive pulmonary aspergillosis is a complication in critically ill patients with acute respiratory distress syndrome, especially those with severe coronavirus disease-associated pneumonia. In this study, five cases of presumed invasive pulmonary aspergillosis in one immunocompromised and four immunocompetent patients with COVID-19 in Buenos Aires are described. In all cases, the underlying conditions, clinical presentation, fungal diagnostic tests used and their results, features of the chest scan images, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…The search yielded a total of 195 articles of which 20 were included 23‐42 . The search strategy and PRISMA flow chart depicting the selection of studies is shown in Figure and Figure 1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The search yielded a total of 195 articles of which 20 were included 23‐42 . The search strategy and PRISMA flow chart depicting the selection of studies is shown in Figure and Figure 1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The main diagnostic criteria used were AspICU [103] (seven studies) and modified AspICU (eight studies) [104]. The patients were predominantly male (49, 66.2%) and had a median age of 69 years (inter-quartile range (IQR) [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The reported major co-morbidities were arterial hypertension (37 patients, 50%), diabetes mellitus (26, 35.1%), chronic pulmonary disease (13, 17.5%), cardiovascular disease (9, 12.2%), and obesity (4, 5.4%).…”
Section: Case Reports and Case Seriesmentioning
confidence: 99%
“…The most frequently isolated Aspergillus species were A. fumigatus (43 cultures, 67.2%) and A. niger (8 cultures, 12.5%), and the most frequent diagnostic samples were bronchoalveolar lavage (BAL) samples (25, 40.3%). Direct examination of respiratory samples showing septate branching hyphae was reported in 11 cases (17.7% of positive cultures) [65][66][67]71,76,[86][87][88][89]92,96,102]. Proven CAPA was reported in five studies: in three cases, the diagnosis was made post portem [69,72,95]; in the remaining two cases, the diagnosis was made using pulmonary tissue (biopsy in one case, lobectomy in the other) [89,92].…”
Section: Case Reports and Case Seriesmentioning
confidence: 99%
“… Distribution ( a ) and co-occurrence ( b ) of fungal species across randomly selected 50 case studies, prospective and retrospective published reports on fungal co-infections in hospitalized COVID-19 patients [ 5 , 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] (also see Supplementary Table S1 ). Searches were done on PubMed (Medline) and Google Scholar using query terms such as “Co-infections”, “coinfections”, “fungi” or “Fungal infections” in combination with either “COVID-19” or “SARS-CoV-2”.…”
Section: Figurementioning
confidence: 99%